Strategi PT Eka Boga Inti Mempertahankan Reputasi Jenama HokBen sebagai Restoran Jepang - Wibowo Irawan, Rozy Putra Pratomo; Annisa Pratama Putri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
To maintain the company reputation is not easy, Moreover, if the company already have good image in public. PT. Eka Boga Inti is the success company that become the restaurant with Japanese Style that even though no Internal parties are Japanese. For decades, PT. Eka Boga Inti has successfully maintain their position as the company with good reputation for restaurant with Japanese Style. This research will examine the strategy of PT. Eka Boga Inti in maintaining their brand reputation as Japanese Restaurant. With Qualitative Method and Data will collected by Interview and Article Observation about PT. Eka Boga Inti. Hope the result of this research will be useful for company that want to maintain their reputation.